Ukrainian food journal. Vol. 6. Issue 3 - National University of Food Technologies (My University, 2017)
An international scientific periodical for the publication of research results of experts in the field of food science, technology and technology, chemistry, economics and management. Міжнародне наукове періодичне видання для публікації результаті досліджень фахівців у галузі харчової науки, техніки та технології, хімії, економіки і управління.
Keywords: food technologies; biotechnology; microbiology; food chemistry; processes and equipment of food productions; харчові технології; біотехнологія; мікробіологія; харчова хімія; процеси і апарати харчових виробництв; пищевые технологии; биотехнология; микробиология; пищевая химия; процессы и аппараты пищевых производств